Aplasia cutis congenita and epidemolysis bullosa: Bart syndrome - Aygun, Abdullah Denizmen; Yilmaz, Erdal; Kurt, Aysegul Nese Citak; Kurt, Abdullah; Elkiran, Ozlem; Okur, Ihsan; Ozercan, Ibrahim (Wiley, 2010)
[Abstract Not Available]